Radiation Safety in the Neonatal Intensive Care Unit: Too Little or Too Much Concern? - Cheng-Chung Yu (Elsevier, 2010)
With rising numbers of extremely premature infants in the neonatal intensive care unit (NICU) who require multiple radiologic examinations for their complex medical conditions, concerns the risk of radiation exposure become a more prevalent issue. The biological effects from cumulative doses of both primary and secondary radiation can be particularly troubling for very premature babies due to their inherent sensitivity to both iatrogenic and environmental insults. Similarly, radiologic studies performed in the NICU pose potentially significant exposure risks to caretakers and to the families of patients often present in the NICU during these examinations. The purpose of this article is to critically review the available literature regarding current exposure rates in the NICU, address the validity of radiation exposure concerns, and suggest areas for improvement. With few exceptions, studies reveal that there were only low doses of radiation derived from any single radiographic examination in standard NICUs and that the radiation dosage used was in compliance with recommendations made by the Commission of European Communities (EC) and International Commission on Radiological Protection (ICRP). However, there were wide variations in the radiation dose per single examination (mean entrance skin doses ranged from 15 to 73.6 μGy) and in the frequency (mean ranged from 3.2 to 31 examinations per infant) of those examinations. Studies also reported low secondary exposure rates from scatter radiation to others present in the NICU during radiographic examinations. Key to limiting unnecessary radiation exposure in the NICU is the employment of proper radiation techniques and safety measures. Thus, adhering to recommendations made by the EC and ICRP can help to reduce the anxiety of patients' families and medical staff regarding their risks from the effects of ionizing radiation in the NICU.